PEMODELAN FAKTOR RISIKO PENYAKIT TUBERKULOSIS - Ratna Juwita; Lia Fentia; Yeffi Masnarivan (LLDIKTI Wilayah X, 2021)
TB disease is still a public health problem today. At least one person will be infected with TB everysecond. The existence of different characteristics of TB patients in Pekanbaru City will lead todifferent health quality and problem burden. One strategy to overcome this is through the method ofgrouping areas in Pekanbaru City which have certain characteristics based on the causes of TB.This study aims to determine the risk factor model for TB disease. This research is a descriptiveanalytic study using secondary data analysis conducted in Pekanbaru City from March to August2020. The data were analyzed using cluster, biplot and discriminant analysis. From the results of thestudy, it was found that 3 sub-district clusters were based on the risk factors for TB. There are 4variables that significantly differentiate between the three clusters, namely the TB prevalencevariable, the number of health workers, the number of health facilities, and the percentage ofmalnourished children under five. The variable number of health workers was the most dominantvariable in differentiating between groups followed by the percentage of under-fives withmalnutrition.